Government Policies on The Development of Sharia Economics and Sharia Business - Muhimah, Uum Ummul; Muin, Fatkhul (Universitas Pahlawan Tuanku Tambusai, 2025)
This research focuses on the state policy towards the development of Islamic business which is part of the existing Islamic economic system. In the current development, the Islamic economy is growing significantly through various policies issued by the government, such as in the field of banking, small and medium enterprises and various kinds of Islamic business products as a form of fulfillment of rights in carrying out basic religious principles. State policy through the Law of the Republic of Indonesia Number 21 of 2008 concerning Sharia Banking is a form of state policy towards the development of Islamic business in society through the fulfillment of regulations and implementation of Islamic business. This research focuses on qualitative research methods by managing data as a source of analysis.